Performance Characteristics of the Cobas Ampliprep/Cobas Taqman V2.0 and the Abbott Realtime Hepatitis C Assays - Implications for Response-Guided Therapy in Genotype 1 Infections. Issue 5 (July 2014) - Taylor, Ninon; Haschke-Becher, Elisabeth; Greil, Richard; Strasser, Michael; Oberkofer, Hannes
Background: With the advent of the protease inhibitors boceprevir and telaprevir a novel therapy approach for HCV genotype 1 infected subjects has become standard of care. Quantification of HCV viral load (VL) represents an important predictor of treatment response. Methods: Two different real-time PCR platforms, the COBAS Ampliprep/COBAS TaqMan v2.0 (CAP-CTM v2.0) and the Abbott RealTime (ART) HCV assay are most widely used. We performed a comparative evaluation of both systems focusing on genotype 1 HCV quantification using clinical specimens, the fourth WHO International Standard for HCV and the Paul Ehrlich National Standard, respectively. Results: The HCV VL assays showed an excellent overall agreement in the clinical specimens studied (R 2 =0.912). Discrepant results were obtained at the low VL end. Four samples tested negative with CAP-CTM v2.0 but were detectable with ART and two samples were undetectable with ART but tested positive with CAP-CTM v2.0. The coefficient of variation in replicate measurements of both reference materials was higher for CAP-CTM v2.0 as compared with ART at the clinical decision point for boceprevir (≥100 IU/ml), but was similar for the two assays at the clinical decision point for telaprevir (≥1, 000 IU/ml). The tendency for underestimation of the diluted standards was higher for ART than for CAP-CTM v2.0. Conclusions: Although both assays allowed accurate determination of VL levels in clinical samples, careful interpretation of results at the low VL end is essential. Furthermore, discontinuation of therapy based on single HCV RNA measurement should be carefully reconciled, unless the issue of assay variability has been addressed adequately.